Oil Palm Empty Fruit Bunch Waste Pretreatment with Benzotriazolium-Based Ionic Liquids for Cellulose Conversion to Glucose: Experiments with Computational Bibliometric Analysis - Ahmad Mudzakir; Karina Mulya Rizky; Heli Siti Halimatul Munawaroh; Dhesy Puspitasari (Indonesian Journal of Science and Technology, 2022)
This study aims to utilize benzotriazolium salt-ionic liquids (ILs) as solvents in the oil palm empty fruit bunch (EFB) waste pretreatment along with bibliometric analysis using VOSviewer. Three ILs have been synthesized and tested as EFB solvents by a microwave-heating method. Those are organic salts of 1,3-methyl-octyl-1,2,3-benzotriazolium ([MOBzt]+) cation with three kinds of anions such as bromide ([Br]-), acetate ([CH3COO]-), and thiocyanate ([SCN]-). The bibliometric analysis showed that new research needs to be conducted to improve the development of research relating to biomass pretreatment. The highest solubility of EFB is in [MOBzt]CH3COO is about 7,5% w/w. The effect of anions on the ability to dissolve EFB is CH3COO-SCN-Br-. When subject to ILs pretreatment, EFB exhibited increased cellulose crystallinity, changed in the structure of cellulose I to cellulose II, reduced particle size, and decreased lignin content compared to untreated one, improving the glucose yield from enzymatic hydrolysis. The highest glucose yield (1,237 mg/mL) was obtained when the EFB was pretreated by [MOBzt]CH3COO with enzymatic hydrolysis for 24 hours. This research is expected to contribute to the development of new biomass pretreatment methods.